Relevância das previsões dos analistas nos diferentes ambientes informacionais dos países emergentes - Peixoto, Emanuelle Priscila de Almeida (2018)
The purpose of this study was to analyze the value relevance of the quality of analysts' forecasts and accounting information in the different information environments of emerging countries, supported by a theoretical framework on information relevance and the signaling of information in the capital market. The data were collected from non-financial companies in the Thomson Reuters Eikon database, which sampled 7,024 companies during the period 2000 to 2016, totaling 35,937 observations for the entire period. The data were analyzed using the linear regression technique, using OLS grouped estimate at country, year and sector level. Firstly, we sought to identify the quality of the analysts' forecasts - QPA and the information environment of the AIP countries, both formed through an index, using the technique of Principal Component Analysis - ACP. Subsequently, it was verified the value relevance of the quality of the analysts' forecasts, as well as their interaction with the accounting information and with the information environment of the countries to explain the stock price, using the model proposed by Collins, Maydew and Weiss (1997). The results suggest that the QPA index is relevant in emerging markets, adding informational content to explain the stock price in these markets. In addition, the study also obtained evidence that, when associated with the quality of analysts' forecasts, accounting information is relevant in these markets. At this point, a greater relevance of equity in relation to earnings per share is highlighted, but it was not possible to find a significant relation between the AIP index and the quality of the analysts' forecasts, not confirming the hypothesis 3 of research, related to the quality of analysts' forecasts is positively related to the information environment in emerging markets, although the study finds support for the positive influence of the information environment of countries on the accuracy of analysts' forecasts in those markets. Also, one can confirm the relevance of the QPA index when associated to the information environment of the emerging countries to explain the variations in the stock price of the analyzed companies. The main contribution of this study is the evidence that the quality of analysts' profit forecasts is value relevant in emerging markets, especially when considered aspects of the informational environment of countries and when associated with accounting information. In this way, it is understood that analysts' forecasts signal information in emerging markets, helping investors to make investment decisions and contributing to the efficiency of these markets.